Nietzsche's system - Richardson, John, 1951- (Oxford University Press, 2002)
This book argues, against recent interpretations, that Nietzsche does in fact have a metaphysical system--but that this is to his credit. Rather than renouncing philosophy's traditional project, he still aspires to find and state essential truths, both descriptive and valuative, about us andthe world. These basic thoughts organize and inform everything he writes; by examining them closely we can find the larger structure and unifying sense of his strikingly diverse views. With rigor and conceptual specificity, Richardson examines the will-to-power ontology and maps the values thatemerge from it. He also considers the significance of Nietzsche's famous break with Plato--replacing the concept of "being" with that of "becoming." By its conservative method, this book tries to do better justice to the truly radical force of Nietzsche's ideas--to demonstrate more exactly theirnovelty and interest